Koran interpreted - "Arberry, Arthur.J." (London, 1963)
No other book ever written, with the possible exception of the Bible, has so dramatically influenced the course of civilization as the Koran. Yet this important text remains little understood in the West.Professor Arberry has rendered the Koran into clear and lyrical English while carefully preserving the incomparable artistry of the Arabic original. "The Koran Interpreted" is universally recognized as not only the most authoritative translation but also the most beautiful one in the English language.
Keywords: Islamic religion